Optimalisasi Kompetensi Kelompok Ibu PKK Guna Mewujudkan Perempuan Berdaya Desa Pantai Cermin, Riau - Marsya, Ulmi; Haris, Aidil; Puji, Ari Andriyas; Putri, Annie Mustika (Jurnal Pengabdian UntukMu NegeRI, 2024)
Community service in Pantai Cermin Village aims to overcome the problem of the lack of competency-based PKK organizational activity and industrial management. This problem was identified through observations and interviews, indicating the urgent need for women's empowerment. The methods used include outreach about the importance of women's empowerment and training covering organizational management, home industry management, and the use of digital technology in marketing. Training activities are designed to improve PKK members' skills in managing organizations and home businesses, as well as utilizing social media and websites for product promotion. The results of this service show a significant increase in the competence of PKK members, who are now more active in managing organizations and home industries. In addition, PKK members also show a higher awareness of their important role in village development. Thus, this program was successful in encouraging women's empowerment and increasing organizational activities in Pantai Cermin Village.